"Ko so s plesom gor jenjáli ..." - Ramovš, Mirko (Traditiones (Ljubljana), 2001)
The author writes about the dance tradition of the Porabje region, focusing on the first data on the subject, its origin, individual dance types and variants, and its anthropological character
Keywords: etnomuzikologija; plesi; Slovenci; Slovenes; Porabje; Hungary; Madžarska; ljudski plesi